ROLE MODEL KEPEMIMPINAN YANG EFEKTIF MENURUT SURAT 1 TIMOTIUS 3 DAN IMPLEMENTASI BAGI KEPEMIMPINAN GEREJA DI ERA 5.0 - Paulus Kunto Baskoro (Manna Rafflesia, 2025)
Leadership is central in God’s church. Whether or not God’s Church develops is an important study in leadership. Leadership becomes a force in making decisions that have a big impact on the progress of God;s church. Problems that arise are often due to the absence of good leadership role models in terms of exemplary life or effectiveness in performance. This results in several things being ineffective in the growth of God’s church. That is why is deemed necessary to examine leadership role models based on 1 Timothy 3 by finding the principles in them. The research method used is a descritiptive qualitative approach. The aim of this research is First, to explain universal leadership studies in the 5.0 era. Second, provide a theological study of leadership role models based on Letter 1 Timothy 3. Third, state the logical implementation for church leaders in the 5.0 era.